Recycled Asphalt Pavement (RAP) as a fully valuable component of the HMA mixes - Koźlarek, Piotr (Budownictwo i Architektura / Civil and Architectural Engineering, 2014)
Currently produced HMA mixes have to meet a certain requirements for a finished product. European product standards and Polish technical guidelines contain all relevant regulations and requirements regarding HMA. Polish technical guidelines WT 2-2010 reduce also the maximum amount of RAP in HMA without taking into consideration the technical capabilities of asphalt mixing plants. There are two main methods to introduce the RAP into HMA at the asphalt mixing plant: cold and hot method. The most popular method in Poland is the cold method, where the cold RAP is added directly to the mixer. According to hot method the RAP is first preheated by using special heating drum, and then added to the mixer. Therefore, an attempt was made to prove, that the HMA with increased content of RAP can compete with HMA made of 100% virgin material. Two HMA mixes designated for traffic category 3 to 4 were selected for further tests, namely asphalt base and binder course. Four variants of every mixture type were made with 0, 15, 25 and 35% of RAP. The virgin added binder was the unmodified asphalt type 35/50. The research plan included testing of each mixture’s volumetric parameters, as well as, their performance-based and performance-related properties.